Avaliação técnica e econômica da inserção de geração fotovoltaica com estratégias de controle em um campus universitário - Calone, Emily Oliveira (2025)
Photovoltaic solar energy has been growing a lot over the years. It is becoming a good source of sustainable energy. It can reduce electricity costs, help small businesses compete, and reduce polluting gas emissions that harm health and the environment. In this situation, it is important for places like the Federal University of Santa Maria (UFSM) to think about using this renewable source in their operations. The present work aims to analyze the electric energy demand and consumption at UFSM, through a study that evaluates the impacts resulting from the insertion of photovoltaic generation on campus. The analyses were performed using the Open Distribution System Simulator (OpenDSS) software, which is integrated with the Python programming language through the Component Object Model (COM) interface. This interface allowed the code and the simulation environment to communicate efficiently. The study had two stages, the first part looks at how adding solar panels affects the results in places where they have already been installed. In the second stage, we suggest adding new solar power plants along with control strategies. This will help reduce reverse power flows and make the most of local generation. The study compares two options: keeping the current setup without control versus adopting new photovoltaic plants with active control. This is done to see which option is better for the institution, taking into account technical aspects and economic benefits. The research also includes information about the university's energy use and the analysis of solar irradiation and the surrounding temperature in Santa Maria during 2017. This analysis is used to determine the operating conditions for the simulations. The study will look at the good and bad effects of adopting photovoltaic energy on campus, proposing practical and efficient solutions that not only reduce energy costs but also promote a cleaner and more sustainable energy matrix, benefiting the university. The results obtained indicate significant gains, especially in scenarios with active inverter control, suggesting a promising strategy for energy efficiency. It is important to continue the studies to confirm the benefits and support future implementation decisions.